(3JaSjQ SYjaGfs - (3eMeO eUWaj GdSYjaGfjs ((3eMeO eUWai GdWQGfSHi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGdg hGdUdGI Ydi SjOfG eMeO s
(3BNQgG (B:s
(3Ef GdeSJMb dLejY dLejY GdeMGeO dceGd PGJg hJaQOg ai UaGJg ZaQ Gddg dg hdhGdOjg hGdeSdejf GLeYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQGdcJH (B/ (3GdbGgQI (B((3JaSjQ (B119) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs